Disclosing the antitumour potential of the marine bromoditerpene sphaerococcenol a on distinct cancer cellular models - Alves, Celso (2022)
Nature has revealed to be a key source of innovative anticancer drugs. This study evaluated the antitumour potential of the marine bromoditerpene sphaerococcenol A on different cancer cellular models. Dose-response analyses (0.1–100 μM; 24 h) were accomplished in eight different tumour cell lines (A549, CACO-2, HCT-15, MCF-7, NCI-H226, PC-3, SH-SY5Y, SK-MEL-28). Deeper studies were conducted on MFC-7 cells, namely, determination of hydrogen peroxide (H2O2) levels and evaluation of apoptosis biomarkers (phosphatidylserine membrane translocation, mitochondrial dysfunction, Caspase-9 activity, and DNA changes). The ability of the compound to induce genotoxicity was verified in L929 fibroblasts. Sphaerococcenol A capacity to impact colorectal-cancer stem cells (CSCs) tumourspheres (HT29, HCT116, SW620) was evaluated by determining tumourspheres viability, number, and area, as well as the proteasome inhibitory activity. Sphaerococcenol A hepatoxicity was studied in AML12 hepatocytes. The compound exhibited cytotoxicity in all malignant cell lines (IC50 ranging from 4.5 to 16.6 μM). MCF-7 cells viability loss was accompanied by H2O2 generation, mitochondrial dysfunction, Caspase-9 activation and DNA nuclear morphology changes. Furthermore, the compound displayed the lowest IC50 on HT29-derived tumourspheres (0.70 μM), followed by HCT116 (1.77 μM) and SW620 (2.74 μM), impacting the HT29 tumoursphere formation by reducing their number and area. Finally, the compound displayed low cytotoxicity on AML12 hepatocytes without genotoxicity. Overall, sphaerococcenol A exhibits broad cytotoxic effects on different tumour cells, increasing H2O2 production and apoptosis. It also affects colorectal CSCs-enriched tumoursphere development. These data highlight the elevance to include sphaerococcenol A in further pharmacological studies aiming cancer treatments.